Forced Resignation of Financial Industry Workers by Employers Judging from The Legislation - Suwinto Johan; Ariawan Gunadi (JURNAL MERCATORIA, 2022)
This study aims to discuss the impact of employer-forced layoffs on employees. Industrial interactions between employees and employers are sometimes a source of contention. In a country's economy, the financial industry plays a critical role. Both parties need each other, yet their tactics are very different. The government is the only party with authority to settle labor-management disputes. Employer-initiated layoffs (PHK) harm the economy, particularly in the country's financial sector and socio-political life. Unemployment will rise as a result of layoffs, causing national instability. Unemployment can lead to riots and other social problems. This discussion is based on the Manpower Law's normative. This research employs a normative legal approach. Forced layoffs or revisions to worker resignations, according to this study, violate the Manpower Act. The rights of workers who wish to resign and workers laid off differ significantly. Instead of layoffs, companies might save money on severance pay by having employees retire. The company's responsibility to give compensation in severance pay and other workers' rights will be eliminated if employees depart. Dispute resolution forums can help workers and employers work out their differences.